The Right to Control The Goods In UAE Law and Rotterdam Rules - Al kohaly, Fouad (Journal of Legal Sciences, 2023)
This research discusses the right of control in accordance with the rules of Rotterdam, and the UAE Maritime Commercial Law No. (26) of 1981 AD, the right of the sender and the consignee to issue instructions to the carrier regarding the goods, and the topic has been divided into two sections, the first topic entitled What is the right of control for seaborne goods, and the second topic It deals with the rights and obligations of the party controlling the seaborne goods. he study concluded with many results and recommendations, including: that the right of the sender to direct and dispose of the goods during the sea voyage is not linked to the right of ownership contained in the goods; Because of their independence, the ownership is transferred during the transportation process according to the general rules, and the carrier does not interfere in that, except for what is related to the consignee as a result of the transfer of ownership, and the right to control is the right to change the course of the goods. The study also concluded that the UAE legislator did not regulate the right of control in a precise manner, as is the case with the Rotterdam Convention, and in order to do so, we suggest that it explicitly stipulate and regulate that right due to its importance.